Electron Irradiation Effects and Defects Analysis of the Upright Metamorphic Four‐Junction (UMM4J) Solar Cells. Issue 6 (21st January 2022) - Zhang, Yanqing; Zhou, Jiaming; Liu, Chaoming; Qi, Chunhua; Wang, Tianqi; Ma, Guoliang; Zhou, Bin; Xiao, Liyi; Huo, Mingxue
Abstract : Herein, 1‐MeV electron irradiation is conducted to the AlGaInP (1.89 eV)/AlInGaAs (1.45 eV)/InGaAs (1.14 eV)/Ge (0.67 eV) upright metamorphic four‐junction (UMM4J) solar cell and its upper three key subcells. Light IV (LIV), external quantum efficiency (EQE), and deep level transient spectroscopy (DLTS) measurements are implemented to analyze the degradation of electric properties and evolution of defects of the UMM4J solar cell. The LIV results illustrate that the short circuit current ( I sc ), open circuit voltage ( V oc ), and maximum power ( P max ) degrade as a function of the logarithmic change of the electron fluence. EQE curves confirm the excellent anti‐irradiation characteristic of the AlGaInP (1.89 eV) subcell. Three types of electron traps E1 ( E c –0.16 eV), E2 ( E c –0.47 eV), and E3 ( E c –0.55 eV) are detected in the AlGaInP subcell. Two types of hole traps H1 ( E v  + 0.35 eV) and H2 ( E v  + 0.70 eV) are discovered in the AlInGaAs subcell and two types of hole traps H3 ( E v  + 0.05 eV) and H4 ( E v  + 0.36 eV) are observed in the InGaAs subcell. Nonionizing energy loss ( NIEL ) of 1‐MeV electrons in are calculated via Screened Relativist method. The defect concentrations show an approximately linear relationship with the displacement dose. Abstract : InGaAs (1.14 eV) subcell is the current limiting junction of UMM4J solar cells for space applications. In InGaAs diodes, a characteristic peak of shallow level majority carrier defect (H3 ) is observed at E v  + 0.05 eV, and the defect concentration increases significantly with the electron fluence. Furthermore, the initial majority carrier defect (H4, E v  + 0.36 eV) increases slightly.